Pembuatan Sistem Informasi Administrasi dan Computer Maintenance Management System pada Perusahaan Ekspedisi X di Surabaya - Levina Nathania Gunawan; Yulia Yulia; Djoni Haryadi Setiabudi (Jurnal Infra, 2018)
PT X is an expedition company in Surabaya. The shipping system that the company offers is a rental system per asset. The company's assets are trucks, forklifts, and dump trucks. Currently, PT X is still using paper records in managing the order placement administration and asset management process.An analysis and design with data flow diagrams and entity relation diagrams are performed before application development begins. The application is created using HTML, PHP, JavaScript, AJAX, Framework Laravel 5.0 MySQL database, and Bootstrap. Developed application contains the features of order placements and Computerized Maintenance Management System.The final result of the application development is the calculation of the order cost, updating of spare part’s price on the stock card when purchasing new spare parts, calculating the cost of maintenance based on the total price of the used spare parts, the scheduled repair reminder based on date periods and intervals.